Teacher solidity in the digital age and its effect on the effectiveness of primary school management - Mawardi Lubis; Alfauzan Amin; Alimni Alimni (Institute of Advanced Engineering and Science, 2023)
Often an era affects a person’s lifestyle in attitude. The attitude of solidity in the digital age is questionable because of its role in the effectiveness of school management. Some other members still believe in contributing to its effectiveness. To overcome these confusions and doubts, research is needed to test whether solidity still plays a role in improving management effectiveness. The purpose of this study was to determine the effect of teacher solidity on the effectiveness of primary school management. Data were collected using quantitative methods. The data collection technique is to use questionnaires. The data were analyzed through Pearson product moments and t-tests. The results of the interpretation of research data showed that teacher solidity has a direct positive effect on the effectiveness of primary school management. The assessment of the results of the study emphasized that solidity cannot be ignored although it is still necessary to have the individual skills of teachers to face the digital age.